Bidirectional introgressive hybridization between a cattle and human schistosome species. - Tine Huyse (Public Library of Science (PLoS), 2009)
Schistosomiasis is a disease of great medical and veterinary importance in tropical and subtropical regions, caused by parasitic flatworms of the genus Schistosoma (subclass Digenea). Following major water development schemes in the 1980s, schistosomiasis has become an important parasitic disease of children living in the Senegal River Basin (SRB). During molecular parasitological surveys, nuclear and mitochondrial markers revealed unexpected natural interactions between a bovine and human Schistosoma species: S. bovis and S. haematobium, respectively. Hybrid schistosomes recovered from the urine and faeces of children and the intermediate snail hosts of both parental species, Bulinus truncatus and B. globosus, presented a nuclear ITS rRNA sequence identical to S. haematobium, while the partial mitochondrial cox1 sequence was identified as S. bovis. Molecular data suggest that the hybrids are not 1st generation and are a result of parental and/or hybrid backcrosses, indicating a stable hybrid zone. Larval stages with the reverse genetic profile were also found and are suggested to be F1 progeny. The data provide indisputable evidence for the occurrence of bidirectional introgressive hybridization between a bovine and a human Schistosoma species. Hybrid species have been found infecting B. truncatus, a snail species that is now very abundant throughout the SRB. The recent increase in urinary schistosomiasis in the villages along the SRB could therefore be a direct effect of the increased transmission through B. truncatus. Hybridization between schistosomes under laboratory conditions has been shown to result in heterosis (higher fecundity, faster maturation time, wider intermediate host spectrum), having important implications on disease prevalence, pathology and treatment. If this new hybrid exhibits the same hybrid vigour, it could develop into an emerging pathogen, necessitating further control strategies in zones where both parental species overlap.